Insights of Nutritional and Anti-nutritional Retention in Traditionally Processed Millets - Sheethal, H. V.; Baruah, Chandrama; Subhash, Kalpuri; Ananthan, Rajendran; Longvah, T. (Frontiers in Sustainable Food Systems, 2022)
Millets are nutritionally superior indigenous staple crops packed with high protein, vitamins, and minerals. However, anti-nutrients such as phytic acid, tannins, and polyphenols present in the millets tend to reduce the bio-accessibility of minerals (iron and zinc), due to which the millet diets are greatly compromised. Although most of the cereals, such as wheat flour, brown rice, and barley, contain phytic acid to a level far more than that of the millets, it is important to develop feasible household methods to reduce the level of phytic acid so as to enhance nutrient absorption. The present study was carried out to investigate the effect of traditional processing on nutrient and anti-nutrient retention of three majorly consumed millets, namely, sorghum, finger millet, and pearl millet. These millets were traditionally cooked and then fermented overnight with water and curd. The results show that this type of simple, traditional household-level process significantly reduced the phytic acid content by 62.9% in sorghum, 34.1% in finger millet, and 29.35% in pearl millet. There is a considerable decrease in phytic acid–zinc molar ratio by 71.38, 61.15, and 33.47% and in phytic acid–iron molar ratio by 73.52, 48.07, and 66.39% in sorghum, finger millet, and pearl millet, respectively. Among the macronutrients, the protein and ash contents were significantly increased. A high retention of water-soluble vitamins was observed in the processed millets. Overall, the traditionally cooked millet, fermented overnight and then added with curd, enhanced many essential macro- and micronutrients and concurrently reduced phytic acid, thus forming a sustainably simple household method for improving dietary nutrients.